Model of Educational Resource Mobilization in Primary Schools under the Office of the Basic Education Commission - Roumsuk, Sittisak; Khantharee, Narech; Singpan, Pongthorn (Ratchaphruek Journal, 2024)
The research article consisted of the following objectives: 1) to study the current conditions in educational resource mobilization primary schools 2) to create a model of educational resource mobilization primary schools 3) to experiment a model of educational resource mobilization primary schools and 4) to evaluate a model of educational resource mobilization primary schools. The group of informants included 1) educational administrators and educational committees, 506 people, 2) experts, 11 people, 3) educational administrator and teachers at Ban Thung Yai School, 19 people, and 4) experts and stakeholders, 21 people. The tools used in the research include: 1) current conditions questionnaire had a reliability value of 0.95 2) model appropriate assessment form, 3) model experiment assessment form, and 4) model assessment form. The statistics used to analyze data were percentage, mean and standard deviation. The results of the research revealed that 1) current conditions in educational resource mobilization primary schools it is at a high level. 2) A model of educational resource mobilization primary schools has 5 components: (1) Principles, (2) Objectives, (3) Methods, (4) Evaluation, and (5) Success Conditions. 3) The overall results of the experiment of using the educational resource mobilization model in primary schools were at a very good level. And 4) The model is appropriate, possibility and usefulness overall is at the highest level.